2018
DOI: 10.22452/adum.vol25no2.5
|View full text |Cite
|
Sign up to set email alerts
|

Autism Spectrum Disorder: Patients’ Oral Health Behaviors and Barriers in Oral Care from Parents’ Perspectives

Abstract: To assess the oral health behaviors of children with Autism Spectrum Disorder (ASD) and explore attitudes and barriers in providing oral care by their parents. A cross-sectional, mixed method study design, which comprised of quantitative and qualitative sections was conducted. The quantitative part assessed the oral health behavior through a parent-proxy report questionnaire whilst the qualitative part assessed parents' overall perspective on maintenance of oral health in children with ASD through an in-depth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 24 publications
0
11
0
3
Order By: Relevance
“…Changing routines to include OH care can also be challenging 25 . Some autistic CYP also have cognitive and motor skills difficulties that can affect their ability to carry out OH behaviours and depend on parents/carers to help them maintain oral hygiene 46 . Parents/carers may have to help their autistic children with a range of daily living tasks and can be overwhelmed when meeting their children's needs, such that OH care falls low on the priority list 41,46 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Changing routines to include OH care can also be challenging 25 . Some autistic CYP also have cognitive and motor skills difficulties that can affect their ability to carry out OH behaviours and depend on parents/carers to help them maintain oral hygiene 46 . Parents/carers may have to help their autistic children with a range of daily living tasks and can be overwhelmed when meeting their children's needs, such that OH care falls low on the priority list 41,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Difficulty in managing children's behaviours, including non‐co‐operation and compliance with dental procedures, was one of the most frequently reported barriers to dental care access cited by parents and dentists. 25 , 27 , 28 , 30 , 32 , 33 , 35 , 36 , 37 , 42 , 43 , 46 , 48 , 53 , 54 , 55 , 56 A US study 33 found that autistic children with more behavioural difficulties had an increased odds of unmet dental needs compared to those with autism who showed behaviours similar to same‐aged peers (odds ratio: 3.35, 95% confidence interval: 1.69, 6.67). The uncooperative behaviours of some autistic children affect the ability of practitioners to carry out the dental procedures needed to care for their teeth, 25 with obvious implications for OH.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations